(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims to measure the relationship and the impact of knowledge management processes to achieve the performance of insurance service, as well as analysis of the reality of the National Insurance Company to identify the level of overall performance, and to achieve this goal, it has been the selection of knowledge management processes according to the survey prepared a supplement to the study (Qubaisi, 2002), and of the four operations (knowledge generation, and storage of knowledge, and the distribution of knowledge, and application of knowledge), which represented the independent variable, and the performance has been the use of quantitative and qualitative measures, (sales growth, customer satisfaction), which represented the dependent variable, and use research to measure these identifying variables prepared Based on the previous studies and additions added by the jury and the researcher. It was intentional sample selection to represent the research community, where distributed the questionnaire to 54 individuals hold positions (b middle and senior management) in the company researched, and measured the performance standards of quality and quantity depending on the statements of financial accounts and records of the company for the period (2009-2013). The data were treated using a combination of statistical methods using the program (Spss), and the use of mathematical equations in applied analysis. The results showed that the company researched performance came wobbling to the lack of attention to the Supreme Administrative leadership management knowledge and application operations and employment in the company’s all business. And that in the light reached to the most important recommendations that work on the application of knowledge management processes essential to the growth of Bargains and customer satisfaction, which in turn achieves outstanding performance of the company surveyed.